When Race/Ethnicity Data Are Lacking Using Advanced Indirect Estimation Methods to Measure Disparities - Fremont, Allen (RAND Corporation, 2016)
This report describes the use of indirect estimation methods, such as Bayesian Indirect Surname Geocoding, to estimate racial/ethnic populations in health care records, which often lack such data, and the use of such methods to measure disparities in quality of care across racial/ethnic groups, as well as to monitor health care utilization and improvement.